Internalisasi Optimisme sebagai Strategi Penguatan Ketahanan Mental Siswa Terhadap Bullying di Sekolah Menengah Pertama - Siti Fauzan Nurjannah; Roni Nugraha (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2026)
This study examines the strategy of internalizing an optimistic mentality in response to the persistent phenomenon of bullying in educational settings. The research focuses on the process of building students' mental resilience through a holistic approach at SMP Bina Taruna, Bandung Regency. The study employs a qualitative approach with phenomenological design, utilizing observation, in-depth interviews with students and teachers, and document analysis as data collection techniques. The findings reveal that: (1) Bullying manifests in three primary forms - verbal, physical, and psychological/relational - representing structural issues within school social dynamics; (2) Students successfully develop an optimistic mentality as a defense mechanism by transforming negative experiences into life lessons, supported by cognitive factors, social support, and spirituality; (3) Schools play a crucial role in fostering collective optimism through character-building programs, teacher exemplification, and peer support systems. The research implies that value internalization-based approaches effectively create resilient school environments. This study makes significant contributions to the development of bullying prevention models through strengthening positive character and transforming traumatic experiences into sources of psychological growth